Radioactive contamination in feral dogs in the Chernobyl exclusion zone: Population body-burden survey and implications for human radiation exposure - Hecla, Jake; Kambarian, Erik; Tubbs, Robert; McKinley, Carla; Berliner, Aaron J.; Russell, Kayla; Spatola, Gabrielle; Chertok, Jordan; Braun, Weston; Hank, Natalia; Marquette, Courtney; Betz, Jennifer; et al. (PloS one, 2023)
This report describes a two-year effort to survey the internal 137 Cs and external β -emitter contamination present in the feral dog population near the Chernobyl nuclear power plant (ChNPP) site, and to understand the potential for human radiation exposure from this contamination. This work was performed as an integral part of the radiation safety and control procedures of an animal welfare oriented trap-neuter-release (TNR) program. The measurement program focused on external contamination surveys using handheld β -sensitive probes, and internal contamination studies using a simple whole-body counter. Internal 137 Cs burden was measured non-invasively during post-surgical observation and recovery. External β contamination surveys performed during intake showed that 21/288 animals had significant, removable external contamination, though not enough to pose a large hazard for incidental contact. Measurements with the whole-body counter indicated internal 137 Cs body burdens ranging from undetectable (minimum detection level ∼100 Bq/kg in 2017, ∼30 Bq/kg in 2018) to approximately 30,000 Bq/kg. A total of 33 animals had 137 Cs body-burdens above 1 kBq/kg, though none posed an external exposure hazard. The large variation in the 137 Cs concentration in these animals is not well-understood, could be due to prey selection, access to human food scraps, or extended residence in highly contaminated areas. The small minority of animals with external contamination may pose a contamination risk allowing exposures in excess of regulatory standards.